Insect eggs trigger systemic acquired resistance against a fungal and an oomycete pathogen. Issue 6 (25th September 2021) - Alfonso, Esteban; Stahl, Elia; Glauser, Gaétan; Bellani, Etienne; Raaymakers, Tom M.; Van den Ackerveken, Guido; Zeier, Jürgen; Reymond, Philippe
Summary: Plants are able to detect insect eggs deposited on leaves. In Arabidopsis, eggs of the butterfly species Pieris brassicae (common name large white) induce plant defenses and activate the salicylic acid (SA) pathway. We previously discovered that oviposition triggers a systemic acquired resistance (SAR) against the bacterial hemibiotroph pathogen Pseudomonas syringae . Here, we show that insect eggs or treatment with egg extract (EE) induce SAR against the fungal necrotroph Botrytis cinerea BMM and the oomycete pathogen Hyaloperonospora arabidopsidis Noco2. This response is abolished in ics1, ald1 and fmo1, indicating that the SA pathway and the N‐hydroxypipecolic acid (NHP) pathway are involved. Establishment of EE‐induced SAR in distal leaves potentially involves tryptophan‐derived metabolites, including camalexin. Indeed, SAR is abolished in the biosynthesis mutants cyp79B2 cyp79B3, cyp71a12 cyp71a13 and pad3‐1, and camalexin is toxic to B. cinerea in vitro . This study reveals an interesting mechanism by which lepidopteran eggs interfere with plant–pathogen interactions.